Which type of fear of cancer progression contributes to the quality of life of Romanian cancer patients during the COVID-19 pandemic? - Kállay, Éva; Medrea, Flavia; Müller-Fábián, Andrea; Dégi, László Csaba (Frontiers in Psychology, 2023)
Fear of cancer progression (FoP) is one of the most frequently reported unmet needs invoked by the majority of cancer patients, which may significantly impair the quality of life (QoL) of patients. The major objective of the present study was to investigate the specificities of the relationship between different dimensions and intensity of FoP and different aspects of patients’ QoL during the COVID-19 pandemic in Romania. A nationwide sample of 330 participants completed a survey, including measures of demographic characteristics, medical variables, QoL, and FoP. Multivariate General Linear and Hierarchical Regression Models were conducted in order to assess the relationship between variables. Our results indicate that less than a quarter of the sample experienced low, between 63%-70% moderate, and 15% high levels of FoP. Our results also indicate that anxiety/worry related to the possibility of progression of the disease, and loss of independence produced significant differences with large effect sizes in all the dimensions of QoL. Our results indicate that besides affective reactions, the fear of cancer survivors to lose independence, not being able to attend to their own lives, seems to be a considerable threat, especially in the context of Romanian health system which has difficulties in offering qualitative psychosocial care for cancer patients. The idea that patients will have to rely on others and may not function well independently, not being able to attend to their own lives, seems to be a considerable threat, next to the experienced affective reactions per se.